Evaluating the Impact of the Free Nutritious Meal Program on Elementary School Students' Pocket Money Allocation: Evaluasi Dampak Program Makan Bergizi Gratis terhadap Pola Pemberian Uang Saku Siswa Sekolah Dasar - Irma Nur Af'idah (Institut Agama Islam Sumatera Barat Pariaman, 2026)
The Free Nutritious Meal (MBG) Program is a government initiative aimed at improving students’ nutritional intake as well as supporting children’s health quality and learning processes at school. This study aims to evaluatethe impact perceived by parents regarding the implementation of MBG Program at the elementary school level. The research employed an outcome evaluation model to assess the results achieved after the program was conducted. . The sampling technique used was random sampling, targeting parents whose children attend elementary school. The instrument validity was ensured through content validity using Aiken’s V index, and construct validity was examined using Exploratory Factor Analysis (EFA). The reliability of the instrument was tested using Cronbach’s Alpha, and the data analysis technique applied was the Spearman Rho correlation test, as the data were not normally distributed. The findings revealed that 71.4% of parents continue to give pocket money to their children, indicating that the program has not significantly reduced pocket money expenditures. However, 86% of parents expressed a positive perception of the MBG program, acknowledging its role in enhancing their children’s motivation to learn and providing nutritious meals. In contrast, in-depth interviews showed that the program’s distribution remains uneven, with several districts in Pati Regency—such as Tayu, Margoyoso, Pati, and Gabus—reporting that the program has not yet been implemented in their schools